Hatred of Democracy: Reflections From Rancière - Silva, Daisy Rafaela da (2016)
This article aims to reflect on democracy in the light of the work entitled "The hatred of democracy" of the philosopher Jacques Rancière. Using the methodology of bibliographical studies, analysis, from Rancière and other critical Bauman ideas, Amartya Sen, Samuel Huntington, sought a study that is current at the issues of the Brazilian Democratic state and political problems , economic and social. The conclusion is brought up in the consolidation of democracy and the ethical management of the state.